An agent-based mechanism to form cloud federations and manage their requirements changes. (24th September 2021) - Bouchareb, Nassima; Zarour, Nacer Eddine
Cloud computing is a business paradigm, where Cloud providers offer computing resources (software and hardware) and Cloud consumers use them. Forming Cloud federations and managing them is a big problem. In this paper, we propose an agent-based mechanism to automatically manage Cloud federations and their requirement changes, to accept the maximum of requests with minimum cost and energy consumption, by soliciting the best Clouds. First, we present two strategies: Offer Strategy and Acceptance Strategy, which allow the formation of federations. Then, we describe how to manage the requirement changes of these strategies. Finally, this paper presents a case study to illustrate our federation management mechanism in Cloud computing. We evaluate the proposed strategies by comparing them with other related works. Simulation results indicate that the proposed policies enhance the provider's profit.